A Project-Based Organizational Maturity Assessment Framework for Efficient Environmental Quality Management - Rashid Al-Marri; Galal Abdalla; Elsadig Mahdi (Systems)
This research aims to develop and validate an organizational maturity framework (OM framework) to assess an organization’s maturity and improve the operational performance of the EQM. The study adopts a multi-methods approach. Qualitative data are sourced from 18 respondents and analyzed through thematic analysis. The analysis reveals that pollution control and energy efficiency are the primary EQM concerns. The maturity assessment occurs through data from one or multiple sources, with the most preferred models being the five-phase models. Finally, maturation has diverse effects on EQM, which mirrors continuous improvement expectations. The quantitative study involved 212 respondents drawn from PBOs across the country. The data were analyzed through SEM, culminating in hypothesis testing. Three of the eight hypotheses were supported, including H4: Legal requirements have a statistically significant impact on PBO maturity (β = −0.150, p = 0.015); H5: Sustainability has a positive statistically significant impact on PBO maturity (β = 0.169, p = 0.045); and H1: the level of maturity determines efficiency in EQM (β = 0.066, p = 0.050). The rest of the variables have an inverse relationship or effects that are not statistically significant. The assessment of weightings for the determinants of PBO maturity culminates in the realization that the variables whose hypothesized relationships were confirmed received moderate priority. These findings explain why the determinants of PBO maturity only explain 8.8% of the variance in maturity, while the entire model explains only 3% of the EQM efficiency. The findings culminate in the validity of the operational instructions for improvement in the task specificity of PBO maturity for EQM performance and an improvement in the conceptualization of EQM efficiency among the PBOs.